2D object segmentation and matching using B-spline model - Wang, Yue (2008)
Including: 2 parts. This thesis presents a research work on object segmentation and matching using a Bspline model. The B-spline is selected here as a curve representation to describe the object contour as it possesses very attractive properties such as compact representation, invariance under affine transformation, local shape controllability, smoothness and continuity. In this thesis, the problem of object segmentation is first addressed and followed by curve matching. In object segmentation, we concentrate on developing a new knowledge-based B-snake model where a series of novel algorithms are proposed and implemented.